2009
DOI: 10.1093/jac/dkp284
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of resistant tuberculosis by nitrate reductase assay performed in three settings in Brazil

Abstract: The data demonstrate that NRA is reliable for susceptibility testing of isoniazid and rifampicin, the two most important drugs for the treatment of tuberculosis. In addition, the reduction in the time necessary to obtain susceptibility results is of fundamental importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
8
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 4 publications
2
8
1
Order By: Relevance
“…NTM were identified initially when readings of DNRA (absence of color) and DPM (growth on PNB containing LJ-slopes) were taken and further confirmed by growth characteristics, pigmentations, and certain biochemical tests. Our results for all four used drugs were also similar to those obtained by other authors with the indirect NRA [28,29] and also comparable with direct NRA [18,20]. We have compared the DNRA assay with those of DPM as Musa et al [26] and INRA with the internationally accepted gold standard IPM.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…NTM were identified initially when readings of DNRA (absence of color) and DPM (growth on PNB containing LJ-slopes) were taken and further confirmed by growth characteristics, pigmentations, and certain biochemical tests. Our results for all four used drugs were also similar to those obtained by other authors with the indirect NRA [28,29] and also comparable with direct NRA [18,20]. We have compared the DNRA assay with those of DPM as Musa et al [26] and INRA with the internationally accepted gold standard IPM.…”
Section: Discussionsupporting
confidence: 88%
“…Additionally, Shikama et al [35] stated 100% sensitivity and specificity of NRA for RIF with a TAT of 15 days. In another study, Shikama et al [18] found the reproducibility of NRA was 100% for INH and EMB and 97% for STR and RIF. Percent agreement between the results of NRA and PM was superb for INH and RIF, i.e., 98.3%.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…The current findings with these two drugs agreed with previous and recent data for nitrate reductase assay (5,21,22), demonstrating insufficient concordance of the assay with the normally recommended standards to recommend them for routine use. Nonetheless, Rosales et al (23) have recently evaluated the nitrate reductase assay for the rapid detection of resistance to secondline drugs such as ofloxacin and kanamycin.…”
Section: Discussionsupporting
confidence: 48%
“…10 The percentage agreement of 98.3%, 98.3%, 90.8% and 93.3% by NRA for INH, RMP, SM and EMB respectively, were observed in Brazilian study. 11 However, marginally lower sensitivity and specifi city for STR and EMB have also been reported. 12,7 For STR and EMB testing, further studies are required to optimize preparation of adequate inoculum and drug concentration in order to avoid strain misclassifi cation.…”
Section: Discussionmentioning
confidence: 99%